Geometry, kinematics and regional significance of faulting and related lamprophyric intrusion in the mineralised zone at the Pu Sam Cap complex, Northwest Vietnam - H., Findlay R. (Vietnam Journal of Earth Sciences, 2018)
The alkali volcanics and intrusive rocks, dated at around 35-33Ma, are cut by mineralised northeast and east trending faults showing predominant evidence for strike-slip. Mineralisation includes haematite-Au-Cu and is accompanied by iron-rich alteration of the volcanic rocks. Detailed assessment of the geometry of the fault system at Pu Sam Cap suggests that the faults formed as a Riedel shear system during left-lateral slip within the Song Hong-Song Chay shear zone and the numerous contemporaneous northwest trending faults to the south; the northeast trending faults are interpreted as dextral “book-end’’ faults between major northwest trending faults enclosing the Pu Sam Cap massif. As mineralisation is hosted within these faults and is also associated with lamprohyric dykes it confirms a thermal event younger than the alkaline volcanics and syenitic intrusives at Pu Sam Cap, suggesting a hidden, young porphyry system. The age of faulting, and thus the maximum age for this young intrusive event, is attributed to the 23-21Ma period of late-stage left-lateral strike-slip motion across northwest Vietnam.ReferencesAnczkiewicz R., Viola G., Muntener O., Thrirlwall M., Quong N.Q., 2007. Structure and shearing conditions in the Day Nui Con Voi massif: implications for the evolution of the Red River Fault. Tectonics 26: TC2002.Cao Shunyun, Liu Junlai, Leis B., Zhao Chunquiang 2010. New zircon U/Pb geochronology of the post-kinematic granitic plutons in Diancang Shan Massif along the Ailao-Shan-Red River Shear Zone and its geological implications. Acta Geologica Sinica (English Edition), 84, 1474-1487.Chung S.-L., Lee T., Lo C.,  et al., 1997. Intraplate extension prior to continental extrusion along the Ailao Shan-Red River shear zone.Geology, 25, 311-314.Cloos H., 1928. Experimentezurinnern Tektonik.  Zentralblatt fur Mineralogie und Palaeontologie, 1928, 609-621.Findlay R.H., Phan Trong Trinh 1997. The structural setting of the Song Ma region, Vietnam, and the Indochina-South China plate boundary problem. Gondwana Research, 1, 11-33.Jolivet L., Beysasac O., Goffe B., Avigad D., Leprevrier C., Maluski H., Ta Trong Thang, 2001. Oligo-Miocene midcrustal subhorizontal shear in Indochina. Tectonics, 20, 46-57.Khuong The Hung 2010. The complex tectonic events and their influence on formation of mineral deposits in northwest Vietnam. Unpublished PhD Thesis, University of Science and Technology, Cracow, 167p.Leloup P.H., N. Arnau,  R. Lacassin, J.R. Kienast, T.M. Harrison, P.T. Trinh, A. Replumaz and P. Tapponnier, 2001. New constraints on the structure, thermochronology and timing of the Ailao Shan - Red river shear zone, SE Asia, J. G. R., 106, 6657-6671.Leloup  PH.., R. Lacassin, P. Tapponnier, U. Scharer, Zhong Dalai, Liu Xaohan, Zhangshan, Ji Shaocheng and PT.Trinh, 1995. The Ailao Shan - Red river shear zone (Yunnan, China), Tertiary transform boundary of Indochina, Tectonophysics, 251, 3-84. Leprevier C., Maluski H., Nguyen Van Vuong, Roques D., Axente V., Rangin C., 1996. Indosinian NW-trending shear zones within the Truong Son belt, Vietnam: 40Ar-39Ar Triassic ages and Cretaceous to Cenozoic overprints. Tectonophysics, 283, 105-107.Lien-Sheng Zhang, Scharer U. 1999. Age and origin of magmatism along the Cenozoic Red River shear belt, China. Contributions to Mineralogy and Petrology, 134, 67-85.Nagy E.A., Scharer U., Minh N.T., 2000. Oligo-Miocene granitic magmatismin central Vietnam and implications for continental deformation in Indochina. Terra Nova, 12, 67-76.Nguyen Thi Bich Thuy, 2016. Isotop dating U-Pb Zircon of Syenit Formation, Pu Sam Cap. Journal of Geology, A Serie, 356, 30-36. (In Vietnamese).Pei-Long Wang, Ching-Hua Lo, Tung-Yi Lee, Sun-ling Chun, Ching-Yan Lan, Nguyen Trong Yem 1998. Thermochronological evidence for the movement of the Ailo Shan-Red River shear zone, a perspective from Vietnam. Geology, 26, 887-890.Phan Trong Trinh, Nguyen Trong Yem, Herve L.P., Tapponnier P., 1994. Late Cenozoic stress fields in North Vietnam from microtectonic measurements. Proceedings of the International Workshop on Seismotectonics and Seismic Hazard in Southeast Asia. Geological Survey of SR Vietnam, Hanoi, 182-186.Riedel W., 1929. Zur Mechanikgreologischer Brucherscheinungen. Zentralblatt fur Mineralogie und Palaeontologie, Abhandlung B, 354-368.Scharer U., Tapponnier P., Lacassin R., Leloup P.H., Dalai Z., Shaosheng J., 1990. Intraplate tectonics in Asia: a precise age for large-scale Miocene movement along the Ailao Shan-Red River shear zone, China. Earth  and Planetary Science Letters, 97, 65-77.Scharer U., Zhang L.S., Tapponnier P., 1994. Duration of strike-slip movements in large shear zones: the Red River belt, China. Earth and Planetary Science Letters, 126, 379-397.Searle M.P., 2006. Role of the Red River Shear zone, Yunnan and Vietnam, in the continental extrusion of SE Asia. Journal of the Geological Society, London, 163, 1025-1036.Searle M.P., Meng-Wan Yeh, Te-Hsien Lin, Sun-Lin Chung, 2010. Structural constraints on the timing of left-lateral shear along the Red River shear zone in the Ailao Shan and Diancang Shan Ranges, Yunnan, SW China. Geosphere, 6, 316-338.Tapponnier P., Lacassin R., Leloup H., Scharer U., Zhong Dalai, Wu Hawei, Liu Ziaohan, Ji Shaocheng, Zhang Lianshang, Zong Jiayou, 1990. The Ailao Shan/ Red River metamorphic belt: Tertiary left-lateral shear between Indochina and south China. Nature, 342, 431-437.Tchalenko J.S., 1970.  Similarities between shear zones of different magnitudes. Bulletin of the Geological Society of America, 81, 1625-1640.Viola G., Anczkiewicz R. 2009. Exhumation history of the Red River shear zone in northern Vietnam:  new insights from zircon and apatite fission-track analysis. Journal of Asian Earth Sciences, 33, 78-90.Yang Yiseng, Hong Qun, Hu Huan-ting, Hieu Pham Trung, Nguyen Thi Bich Thuy, Chen Fu-kun, 2013. Geochemical characteristics and genesis of the Cenozoic porphyry in the Laizhou area, northwestern Vietnam. Acta Petrologica Sinica, 29(3), 899-911. (In Chinese with English abstract, full English version through Google Translate).